2019
DOI: 10.1002/mdc3.12841
|View full text |Cite
|
Sign up to set email alerts
|

Successful Management of Anti‐mGluR1 Encephalitis with Immunosuppressive Treatment: Dengue Virus as a Trigger?

Abstract: View Supplementary Video 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…However, one case was preceded by herpes zoster infection in the trigeminal nerve a month before the disease onset, another was preceded by streptococcal pharyngitis 2 months prior, and yet another case was found to have evidence of dengue virus infection. These findings suggest a post-infectious element in the occurrence of anti-mGluR1 encephalitis or that infection may trigger its onset ( 4 , 14 , 15 ). Unlike most autoimmune disorders which favor women, coincident autoimmunity in anti-mGluR1 encephalitis patients affected both genders equally ( 26 ).…”
Section: Discussionmentioning
confidence: 85%
“…However, one case was preceded by herpes zoster infection in the trigeminal nerve a month before the disease onset, another was preceded by streptococcal pharyngitis 2 months prior, and yet another case was found to have evidence of dengue virus infection. These findings suggest a post-infectious element in the occurrence of anti-mGluR1 encephalitis or that infection may trigger its onset ( 4 , 14 , 15 ). Unlike most autoimmune disorders which favor women, coincident autoimmunity in anti-mGluR1 encephalitis patients affected both genders equally ( 26 ).…”
Section: Discussionmentioning
confidence: 85%
“…This patient concomitantly had Hodgkin lymphoma (Ophelia syndrome) ( 15 ). In addition, in Guadaloupe, a case of anti-mGluR1 encephalitis that presented with acute cerebellar ataxia was associated with a possible trigger by dengue virus infection ( 16 ).…”
Section: Resultsmentioning
confidence: 99%
“…Research by Khojah et al ( 4 ) highlighted that 25% of patients experienced one or more prodromal symptoms—ranging from fever, headache, and fatigue to weight loss, nausea, vomiting, night sweats, and flu-like manifestations—with a median interval of 30 days leading up to neurological symptom onset. In a literature review, three patients reported prior infections, including a trigeminal herpes zoster infection a month before onset ( 5 ), a streptococcal pharyngitis 2 months prior ( 6 ), and a dengue virus infection ( 7 ). The link between such infections and anti-mGluR1 encephalitis remains ambiguous.…”
Section: Discussionmentioning
confidence: 99%